Phytoremediation of liquid wastes of Al-Kharrazie valley.Mosul - Abdulazeez Al-safawi; Wafaa Al-Sanjery (College of Education for Pure Sciences, 2018)
The purpose of this study was to evaluate the quality of wastewater running through Al-Kharrazie, a seasonal rain water valley in Mosul city which considered now as a sewerage channel discharging their influents into Tigris river at Al-Ghabat region.            Physical, chemical and biological testes were run to evaluate its discharges quality, the results revealed high pollution loads, reflects by BOD5،TDS، PO4 and NO3 which reached to (120,572,2.352 and2.319) mgL respectively. Also, it shows that high total plate count TPC, F.coliformaandBEsherishiaBcolirreaching(1071*105cellml,110*105and110*105cell100ml)respectively.Phytoremediation was going on passing through the valley to certain extent, reflected by the   drop in the main pollutant parameters of BOD5, PO4, NO3,TPC,F.coliform and E. coli  by (57, 19, 11, 89, 93, 93)%Grespectively.